2017
DOI: 10.1177/0033294117732344
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Pseudo Winning or Losing Streak on Mental Attitudes and the Evaluation of Results

Abstract: Although human motivation has been well studied, studies manipulating human motivation are scarce. The present study aimed to induce the hot-hand phenomenon using a pseudo success situation. Under the framework of the two-factor theory of emotion, we investigated the effect of a deviant situation, such as continuously winning or losing, on mental attitudes and the evaluation of the results using the contingent-negative variation (CNV) and feedback-locked P3 (FB-P3). The CNV is a neural activity that reflects e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Standard ERP recording methods indicated that P2 component was sensitive to the onset of pleasant-going arousal-related amplitude modulation persisting until stimulus offset (Carretié et al, 2001a , b ; Amrhein et al, 2004 ; Olofsson and Polich, 2007 ; Olofsson et al, 2008 ). Kamei et al ( 2018 ) also observed that the auditory P2 and the occurrence of pleasant emotions were higher in the winning streak (WS) condition than in the losing streak (LS) condition (Kamei et al, 2018 ). Similar to Kamei et al ( 2018 ), a larger P2 peak-amplitude from 150 to 220 ms was observed in CWHP compared with CLHP condition, might because CW elicited more positive emotions than CL and this emotion state was lasting then continuously influenced subjects' price perception resulting higher adding ratio of CWHP than CLHP (see Figures 4 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard ERP recording methods indicated that P2 component was sensitive to the onset of pleasant-going arousal-related amplitude modulation persisting until stimulus offset (Carretié et al, 2001a , b ; Amrhein et al, 2004 ; Olofsson and Polich, 2007 ; Olofsson et al, 2008 ). Kamei et al ( 2018 ) also observed that the auditory P2 and the occurrence of pleasant emotions were higher in the winning streak (WS) condition than in the losing streak (LS) condition (Kamei et al, 2018 ). Similar to Kamei et al ( 2018 ), a larger P2 peak-amplitude from 150 to 220 ms was observed in CWHP compared with CLHP condition, might because CW elicited more positive emotions than CL and this emotion state was lasting then continuously influenced subjects' price perception resulting higher adding ratio of CWHP than CLHP (see Figures 4 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kamei et al ( 2018 ) also observed that the auditory P2 and the occurrence of pleasant emotions were higher in the winning streak (WS) condition than in the losing streak (LS) condition (Kamei et al, 2018 ). Similar to Kamei et al ( 2018 ), a larger P2 peak-amplitude from 150 to 220 ms was observed in CWHP compared with CLHP condition, might because CW elicited more positive emotions than CL and this emotion state was lasting then continuously influenced subjects' price perception resulting higher adding ratio of CWHP than CLHP (see Figures 4 , 6 ). In addition, larger LPP amplitudes had been observed in CWHP compared to CLHP either (see Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation